EVIDENCE FOR A 20° TILTING OF THE EARTH'S ROTATION AXIS 110 MILLION YEARS AGO - Prevot M.; Mattern E.; Camps P.; Daignieres M. (My University, 2000)
True polar wander (TPW), the shift of the Earth’s rotation axis with respect to the entire globe, is most probably due to mass redistribution in the Earth’s mantle as a result of convection. Using a new rigorously selected paleomagnetic database gathering only directions obtained from magmatic rocks, we find that TPW has been clearly intermittent over the last 200 Myr with two long periods of strict standstill from the present to 80 Ma and from approximately 150 to 200 Ma. A single period of shifting is observed, between 80 and about 150 Ma. This period culminates around 110 Ma in an 20° abrupt tilting during which an angular speed exceeding 5°/Myr (0.5 m/yr) may have been reached. Assuming that the time-averaged geomagnetic field is axial, our results indicate that the changes in the position of the rotation axis, and therefore in the inertia tensor of the Earth, are intermittent. We suggest that a major reorganization of the mass distribution in the Earth’s mantle occurred in the Lower Cretaceous. This event, concomitant with plume hyperactivity at the Earth’s surface and probable drastic changes at the core–mantle boundary attested by the inhibition of geomagnetic reversals, suggests unmixing of upper and lower mantle by avalanching of upper mantle material down to the core–mantle boundary. The astonishingly strict stability of the time-averaged position of the rotation axis before and after this episode of shifting implies the existence of some steady convection which does not modify the large-scale distribution of mass within the mantle. Given the intermittence of mantle avalanching, we suggest that these long periods of stability correspond to the temporary reestablishment of a basically two-layered convection system within the mantle.
Keywords: Cretaceous; Mesozoic::Cretaceous; Мезозой::Меловая